"From Victimhood to Warriors": Super-researchers' Insights Into Alzheimer's Disease Clinical Trial Participation Motivations. (19th July 2019) - Bardach, Shoshana H; Parsons, Kelly; Gibson, Allison; Jicha, Gregory A
Abstract: Background and Objectives: Recruitment and retention of research participant serve as a significant challenge in the search for ways to slow or prevent Alzheimer's disease. While barriers to participation are well documented, less is known about motivations for Alzheimer's disease clinical research participation. The purpose of this study was to explore what motivates individuals—who ultimately develop an ongoing connection to research and frequently participate—to engage and stay involved in Alzheimer's disease research. Research Design and Methods: Individuals who had participated in multiple Alzheimer's disease-related clinical trials, or their study partners, were interviewed about their decisions to engage and remain in research. Findings: Interviews were completed with 33 individuals, 28 research participants, and 5 study partners. All interviews were audio-recorded and transcribed verbatim for analysis. Respondents indicated learning about research opportunities through the media, community events, doctors, and other research participants. While many were initially motivated by a family history or knowing someone with Alzheimer's disease, others had no personal exposure. Individuals in prevention studies were generally proactive and viewed research as a constructive way to address memory concerns. While several individuals acknowledged personal benefits of research participation, most indicated an understanding of the importance of research and being motivated to help others in the future, frequently referencing a sense of social responsibility or moral obligation to help. Positive relationships with personnel at the site encouraged continued involvement. Discussion and Implications: These findings suggest that efforts to identify research participants should highlight the value of research and help illuminate how participation may contribute to well-being of future generations.